2008
DOI: 10.1111/j.1540-5915.2008.00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Antecedents and Consequences of CIO Strategic Decision‐Making Authority: An Empirical Study*

Abstract: Despite the strategic importance of information technology (IT) to contemporary firms, chief information officers (CIO) often still have varying degrees of strategic decisionmaking authority. In this study, we apply the theory of managerial discretion to define CIO strategic decision-making authority and argue that the CIO's level of strategic decision-making authority directly influences IT's contribution to organization performance. We also draw on the power and politics perspective in the strategic decision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 96 publications
3
76
1
1
Order By: Relevance
“…Organisational position of the CIO is most often considered in terms of structural power i.e. the rank of the CIO reflected by reporting level (Banker et al, 2004;Karimi et al, 1996), and in terms of political relationships reflected by the frequency of the CIO's interaction with the chief executive of the organisation, and the CIO's active involvement in the organisation's top management team (TMT) (Armstrong & Sambamurthy, 1999;Smaltz et al, 2006;Preston, Chen & Leidner, 2008).…”
Section: Cio Organisational Positioningmentioning
confidence: 99%
See 4 more Smart Citations
“…Organisational position of the CIO is most often considered in terms of structural power i.e. the rank of the CIO reflected by reporting level (Banker et al, 2004;Karimi et al, 1996), and in terms of political relationships reflected by the frequency of the CIO's interaction with the chief executive of the organisation, and the CIO's active involvement in the organisation's top management team (TMT) (Armstrong & Sambamurthy, 1999;Smaltz et al, 2006;Preston, Chen & Leidner, 2008).…”
Section: Cio Organisational Positioningmentioning
confidence: 99%
“…Power stems from authority and is inherent in the official position of managers and executives. Structural power provides the CIO with a legitimate base for influencing organisational action (Preston et al, 2008). However, since IS&T implementations are organisational in scope and affect processes and structures across organisations, it has also been suggested that CIOs need to gain commitment of fellow TMT members for IS&T induced changes (Enns, Huff & Golden, 2001 (Eisenhardt & Bourgeois, 1988).…”
Section: Research Modelmentioning
confidence: 99%
See 3 more Smart Citations